Cell-penetrating peptide-conjugated antisense oligonucleotides restore systemic muscle and cardiac dystrophin expression and function - Yin, HaiFang (Hum Mol Genet, 2008)
Antisense oligonucleotides (AOs) have the potential to induce functional dystrophin protein expression via exon skipping by restoring in-frame transcripts in the majority of patients suffering from Duchenne muscular dystrophy (DMD). AOs of morpholino phosphoroamidate (PMO) and 2′-O-methyl phosphorothioate RNA (2′Ome RNA) chemistry have been shown to restore dystrophin expression in skeletal muscle but not in heart, following high-dose systemic delivery in murine models of muscular dystrophy (mdx). Exploiting the cell transduction properties of two basic arginine-rich cell penetrating peptides, we demonstrate widespread systemic correction of dystrophin expression in body-wide muscles and cardiac tissue in adult dystrophic mdx mice, with a single low-dose injection of peptide-conjugated PMO AO. This approach was sufficient to restore uniform, high-level dystrophin protein expression in peripheral muscle and cardiac tissue, with robust sarcolemmal relocalization of the dystrophin-associated protein complex and functional improvement in muscle. Peptide-conjugated AOs therefore have significant potential for systemic correction of the DMD phenotype.